Synthesis and Characterization of Pure and Nano-Ag Impregnated Chitosan Beads and Determination of Catalytic Activities of Nano-Ag - Zahoor Ahmad; Maryam Maqsood; Mazher Mehmood; Mirza Jameel Ahmad; Muhammad Aziz Choudhary (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2017)
The synthesis of nano-Ag impregnated porous Chitosan beads, in crosslinked and uncrosslinked forms, was aimed to investigate their catalytic potential in reducing nitro group into amino by NaBH4. The material was found unique concerning the synthesis of well-defined Ag NPs and subsequently adsorbing them on its surface. The crosslinked and uncrosslinked chitosan beads were separately analyzed for the loading of Ag and its effect over the microstructures of the substrate. BET was used to explore the porous nature and pore size distributions of beads. At each stage, SEM coupled with EDX, FT-IR, and inductively coupled plasma (ICP) were employed to characterize the material. The catalytic activities of nano-Ag in crosslinked and uncrosslinked beads were determined by the reduction of 4-Nitrophenol (4-NP) into 4-aminophenol (4-AP) by NaBH4; which is least effective for such reduction. The catalytic activities were monitored by UV-Vis spectrophotometer. The results demonstrated the nano-Ag as a reliable and active catalyst which made NaBH4 quite capable for the nitro reduction. Moreover, the catalytic activities of crosslinked chitosan substrate were found more reproducible as compared to the uncrosslinked substrate.